HUMAN HEALTH AND POLLUTION: मानव स्वास्थ्य एवं प्रदूषण - Verma, Pratibha; Katiyar, Alka (International Journal of Research -GRANTHAALAYAH, 2015)
Environment refers to the entire physical and biological world. In which organisms live, grow, thrive and develop their natural tendencies. The truth is that the existence of life is basically dependent on the environment. Changes in the physical, chemical or biological characteristics of any element of the environment that are harmful to humans or other beings is called environmental pollution. Environmental pollution has taken the form of a worldwide problem today and in India also this problem is seen in various forms. Due to industrial and technological development, rapid population growth, urbanization etc., the environmental pressure started increasing. Today, the greatest need is "destruction-free development" but due to human activities, environmental imbalance increases, which pollutes the environment and endangers the existence of other animals and flora including humans. Environmental pollution affects human health, causing fatal diseases. पर्यावरण का तात्पर्य समूचे भौतिक एवं जैविक विश्व से है। जिसमें जीवधारी रहते हैं, बढ़ते हैं, पनपते हैं और अपनी स्वाभाविक प्रवृत्तियों का विकास करते हैं। सत्य तो यह है कि जीवन का अस्तित्व मूलतः पर्यावरण पर निर्भर है। पर्यावरण के किसी भी तत्व के भौतिक, रासायनिक अथवा जैविक विशेषताओं में परिवर्तन जो मानव या अन्य प्राणियों के लिए हानिकारक हो पर्यावरण प्रदूषण कहलाता है। पर्यावरण प्रदूषण आज एक विश्वव्यापी समस्या का रूप ले चुका है और भारत में भी यह समस्या विविध रूपों में दृष्टिगत होती है। औद्योगिक एवं तकनीकी विकास, तीव्र जनसंख्या वृद्धि, शहरीकरण आदि के कारण पर्यावरण के दबाव में निरन्तर बढ़ोतरी होने लगी। आज सबसे बड़ी आवश्यकता है ‘‘विनाश रहित विकास’’ किन्तु मानवीय क्रियाकलापों से पर्यावरणीय असंतुलन बढ़ता ही जाता है जिससे पर्यावरण प्रदूषित हो जाता है और मानव सहित अन्य प्राणियों एवं वनस्पतियों का अस्तित्व खतरे में पड़ता जा रहा है। पर्यावरण प्रदूषण मानवीय स्वास्थ्य को प्रभावित करता है जिससे घातक रोग उत्पन्न होते हैं।